2022
DOI: 10.3389/fmicb.2022.832213
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms in Water Hoses of a Meat Processing Environment Harbor Complex Microbial Communities

Abstract: Safe and hygienic water distribution is essential for maintaining product quality and safety. It is known that biofilms alter the appearance and microbial quality of water along the distribution chain. Yet, biofilms in water hoses throughout the food processing environment have not been investigated in detail. Here, microbial communities from water hoses and other environmental sites in contact with water, in addition to the source water itself, were studied in the meat processing environment. Biofilms were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…The ability of many bacteria to form biofilms is influenced by other species on surfaces due to many ecological interactions. A number of recent studies cataloging bacterial diversity on food contact surfaces and studying bacterial interspecies interactions have concluded that biofilms in the food industry are often comprised of multiple species that interact with each other mainly due to metabolic and physiological needs ( Wagner et al, 2021 ; Nan et al, 2022 ; Voglauer et al, 2022 ). In our trial, 35% of the isolates turned out to be strong biofilm formers which shows that many species probably co-existed on surfaces with other resident microbiota as a result of positive or negative associations.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of many bacteria to form biofilms is influenced by other species on surfaces due to many ecological interactions. A number of recent studies cataloging bacterial diversity on food contact surfaces and studying bacterial interspecies interactions have concluded that biofilms in the food industry are often comprised of multiple species that interact with each other mainly due to metabolic and physiological needs ( Wagner et al, 2021 ; Nan et al, 2022 ; Voglauer et al, 2022 ). In our trial, 35% of the isolates turned out to be strong biofilm formers which shows that many species probably co-existed on surfaces with other resident microbiota as a result of positive or negative associations.…”
Section: Discussionmentioning
confidence: 99%
“…Hotspot contamination, conversely, referred to surfaces with repeated L. monocytogenes detection that potentially represented persistent colonies employing stress tolerance mechanisms and biofilm formation [12]. Pre-existing contamination control strategies, such as disinfection of food contact surfaces, may consequently corral Listeria to hotspot contamination surfaces that are improperly cleaned, such as drains and floors, or difficult to decontaminate such as nozzles, hoses, and machines with obstructive designs [12,63]. Lastly, widely disseminated contamination referred to situations in which large areas of the facility produced positive results for detection of L. monocytogenes.…”
Section: Occurrence Of Listeria From Primary Food Production To Retailmentioning
confidence: 99%
“…Zhang et al 10.3389/fmicb.2022.993237 Frontiers in Microbiology 08 frontiersin.org formation is another important survival model for microorganisms. When the number of bacteria fixed on the surface of host cells increases, the bacteria can secrete extracellular compounds, such as polysaccharides and protein, eventually forming stable biofilms (Voglauer et al, 2022). Zhao et al (2022) exhibited that acidic electrolysed water disturbed the biofilm formation of E.coli by decreasing the nucleotide-related and carbohydrates component.…”
Section: Flagellar Assembly and Biofilm Formationmentioning
confidence: 99%